2019
DOI: 10.1007/s40610-019-0110-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fibroblast Growth Factor 23 by Iron, EPO, and HIF

Abstract: Purpose of review: Fibroblast growth factor-23 (FGF23) is the key hormone produced in bone critical for phosphate homeostasis. Elevated serum phosphorus and 1,25dihydroxyvitaminD stimulates FGF23 production to promote renal phosphate excretion and decrease 1,25dihydroxyvitaminD synthesis. Thus completing the feedback loop and suppressing FGF23. Unexpectedly, studies of common and rare heritable disorders of phosphate handling identified links between iron and FGF23 demonstrating novel regulation outside the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 111 publications
1
21
0
Order By: Relevance
“…The expression levels were quantified and the results confirmed that B[a]P was able to dose-dependently reduce the expression ( Figure 6 M). We also detected another Hif target gene, epo ( Figure 6 G–L), which is expressed in brain during embryogenesis and is functionally associated with neural differentiation and proliferation [ 38 , 39 , 40 ]. The quantitative results indicated that the expression of epo was also dose-dependently reduced by B[a]P treatment ( Figure 6 N), and the effect sizes at each dose were similar to those for hif2a in B[a] P- treated embryos.…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels were quantified and the results confirmed that B[a]P was able to dose-dependently reduce the expression ( Figure 6 M). We also detected another Hif target gene, epo ( Figure 6 G–L), which is expressed in brain during embryogenesis and is functionally associated with neural differentiation and proliferation [ 38 , 39 , 40 ]. The quantitative results indicated that the expression of epo was also dose-dependently reduced by B[a]P treatment ( Figure 6 N), and the effect sizes at each dose were similar to those for hif2a in B[a] P- treated embryos.…”
Section: Resultsmentioning
confidence: 99%
“… 23 For example, the tissue-specific alternative splicing in D3 of FGFR1, FGFR2, and FGFR3 can generate b and c isoforms, and thus determines the binding specificity/promiscuity for individual FGFs at diverse cells and tissues. 24 Furthermore, it is well documented that epigenetic mechanisms, 25 the posttranslational modifications, such as phosphorylation, 26 glycosylation, 27 ubiquitination, 28 and cellular trafficking of FGFs/FGFRs 29 , 30 are also involved in the regulation of the expressions of FGF/FGFR signaling components and the signal specificity, intensity, and timing.…”
Section: Introduction Of the Fgf/fgfr Signalingmentioning
confidence: 99%
“…Another potential threat is that HIF stabilization may be associated with an increase in circulating fibroblast growth factor 23 (FGF23) level, and high concentrations of FGF23 have been associated with cardiovascular complications and bone mineralization disorders. However, the increase in FGF23 caused by HIF-PHI is lower than its increase after administration of ESAs [69,70].…”
Section: Fig 2 Direct and Indirect Hepcidin Inhibitorsmentioning
confidence: 84%